2016
DOI: 10.1111/ecin.12411
|View full text |Cite
|
Sign up to set email alerts
|

Brides for Sale: Cross‐border Marriages and Female Immigration

Abstract: Developed East Asian countries import a large number of women from abroad as brides every year, although such cross‐border marriages virtually did not exist 20 years ago. With a theoretical framework and empirical evidence, we argue that developed Asian countries' demand for foreign brides is the consequence of improvement in women's economic status and gender‐discriminative household arrangements that insufficiently incorporate women's improved status in marriage. We offer sets of empirical evidence in line w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 48 publications
1
24
0
1
Order By: Relevance
“…The results suggest that the number of cross‐border marriages increased rapidly in the early 2000s but has declined mildly since the mid‐2000s, perhaps because of a combination of (A) strict governmental regulations on international marriage brokers and visa inspection, and (B) some amount of saturation in the demand for foreign wives. Also, in accordance with existing literature (Edlund et al., ; Jones, ; Kawaguchi & Lee, ; Lee, Seol, & Cho, ), the current study found that the majority of cross‐border marriages in Korea occur between local men, who are more likely to have a low level of educational attainment, and women from developing countries in Southeast Asia. The low socioeconomic status of the local groom raises concerns about potential marginalization of multicultural families and the exacerbation of social inequality in subsequent generations.…”
Section: Discussionsupporting
confidence: 92%
“…The results suggest that the number of cross‐border marriages increased rapidly in the early 2000s but has declined mildly since the mid‐2000s, perhaps because of a combination of (A) strict governmental regulations on international marriage brokers and visa inspection, and (B) some amount of saturation in the demand for foreign wives. Also, in accordance with existing literature (Edlund et al., ; Jones, ; Kawaguchi & Lee, ; Lee, Seol, & Cho, ), the current study found that the majority of cross‐border marriages in Korea occur between local men, who are more likely to have a low level of educational attainment, and women from developing countries in Southeast Asia. The low socioeconomic status of the local groom raises concerns about potential marginalization of multicultural families and the exacerbation of social inequality in subsequent generations.…”
Section: Discussionsupporting
confidence: 92%
“…Examining cultural discourses about marriage‐labor immigrants in Korea has implications beyond the borders of Korea because similar demographic changes are occurring in other parts of East Asia. For example, Taiwan (Bélanger et al ; Tsai et al ) and Singapore (Yeoh et al ) have both witnessed a rapidly increasing number of marriage‐labor immigrants, predominantly from China, Vietnam, and the Philippines (Jones and Miller‐Chair ; Kawaguchi and Lee ). A number of studies have addressed the complexities of marriage‐labor immigration in East Asia by investigating key patterns among immigrants including gender, age, ethnicity, the level of education, citizenship changes, and social status (e.g., see Jones and Miller‐Chair ; Yeoh et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this view, Kawaguchi and Lee (2015) provide an explanation as to why economically successful women tend to remain unmarried in East Asian countries. They show that recent "marriage immigration" (i.e., the immigration of women from less developed countries in order to marry men in more developed countries) is accounted for by (i) advancements in women's socioeconomic status in developed countries and (ii) insufficient adjustment to the cultural norms affecting the division of labor within a marriage, resulting in more women deciding to remain unmarried to avoid the additional burdens that marriage would entail.…”
Section: Endnotesmentioning
confidence: 99%